Strategi Pengembangan Usaha Ternak Sapi Potong pada Kelompok Ternak Lembu Makmur Desa Gunungsari Kecamatan Dawarblandong Kabupaten Mojokerto - Assyarif, Hilmy Mufid; Yuliati, Nuriah; Atasa, Dita (Universitas Galuh, 2024)
This research aims to identify internal and external factors that influence the beef cattle business and determine strategies that can be used to develop the beef cattle business in KT Lembu Makmur. In identifying the value of internal and external environmental factors the author uses the IFE and EFE Matrix. Formulation of alternative strategies for livestock groups using SWOT analysis and determining strategic priorities using QSPM analysis. The results of the IFE analysis show a value of 2.39 and an EFE of 2.59 which results in the Competitive Position Matrix of the livestock business being in the White Area. From these results it can be concluded that KT. Lembu Makmur is in a quite profitable position so that it can carry out the S - O (Strength - Opportunities) strategy. The S - O strategy included in the QSPM matrix produces the highest value of 1.02 with the strategic priority of developing human resources.